Laplace Transform of Shifted Dirac Delta Function/Proof 1

From ProofWiki
Jump to navigation Jump to search


Let $\map \delta t$ denote the Dirac delta function.

The Laplace transform of $\map \delta {t - a}$ is given by:

$\laptrans {\map \delta {t - a} } = e^{-a s}$


\(\ds \laptrans {\map \delta {t - a} }\) \(=\) \(\ds \int_0^{\to +\infty} e^{-s t} \map \delta {t - a} \rd t\) Definition of Laplace Transform
\(\ds \) \(=\) \(\ds e^{-s \times a}\) Integral to Infinity of Shifted Dirac Delta Function by Continuous Function
\(\ds \) \(=\) \(\ds e^{-a s}\)